A Robust Nanoparticle Platform for RNA Interference in Macrophages to Suppress Tumor Cell Migration - Liang, Shi; Zheng, Junmeng; Wu, Wei; Li, Quan; Saw, Phei Er; Chen, Jianing; Xu, Xiaoding; Yao, Herui; Yao, Yandan (Frontiers in Pharmacology, 2018)
Macrophages are one of the most abundant immune cells in the solid tumor and their increased density is associated with the specific pathological features of cancers, including invasiveness, metastasis, immunosuppression, neovascularization, and poor response to therapy. Therefore, reprogramming macrophage behavior is emerging as a promising therapeutic modality for cancer treatment. RNA interference (RNAi) technologyis one of the powerful strategies for the regulation of macrophage activities by silencing specific genes. However, as polyanionic biomacromolecules, RNAi therapeuticssuch as small interfering RNA (siRNA) cannot readily cross cell membrane and thus specific delivery vehicles are required to facilitate the cytosolic siRNA delivery.Herein, we developed a robust nanoparticle (NP) platform for efficient siRNA delivery and gene silencing in macrophages. This NP platform is composed of biodegradable poly(ethylene glycol)-b-poly(ε-caprolactone) (PEG-b-PCL), poly(ε-caprolactone)-b-poly(2-aminoethylethylene phosphate) (PCL-b-PPEEA), and PCL homopolymer. We chose CC-chemokine ligand 18 (CCL-18) as a proof of concept therapeutic target and our results demonstrate that the CCL-18 silencing in macrophages can significantly inhibit the migration of breast cancer cells. The successful regulation of the macrophage behavior demonstrated herein shows great potential as an effective strategy for cancer therapy.